MENJADI KOTA DEFINITIF - Nurhadi Sasmita (Program Studi Ilmu Sejarah Fakultas Ilmu Budaya Universitas Jember, 2019)
Abstract : Jember as the most rapid growth city in Besuki Residency. Traditionally Jember has actually existed, but turned into a definitive modern city after being inhabited and managed by the Dutch. The capital invested in Jember to develop the plantation encourages the growth and development of other sectors so that Jember is developing very rapidly. This study seeks to reconstruct the changes and dynamics of Jember into a modern city and the evidence of infrastructure that supports it. NV LMOD has an important role in the process. The method used is the method of history, including heuristic stages, criticism, interpretation, and historiography. The approach used is government administration, especially on decentralization. Keywords : City of Jember, plantation, NV LMOD, exploitation.